Pengembangan Perencanaan Jaringan Bisnis Yang Efektif Makanan Cepat Saji Pada Produk Harumaki Beef - Resya Dwi Marselina; Alya Meisya Ichwanda; Demila Eva Yulianti; Eros Rosdiana; Radiyallah Khairunnisa; Salimah Arif Nur Kamilah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to develop and plan an effective business network for the lumpia beef business, especially in building a business network so that the lumpia beef business can continue to grow. This research uses qualitative research methods with a descriptive approach. The source of data used in this study is primary data. Data collection is done through observation and documentation. Observation in this study was carried out by observing consumer tastes and documentation was carried out by collecting data on effective business networks. The subject of this research is business development through business networks and the object is the Harumaki Beef business. Based on the results of research on the development of effective business networks for Harumaki Beef, it can be concluded that the development of Harumaki Beef can be done effectively if Harumaki Beef can be marketed online so that it can be more widely known by the public by strengthening its business network.